2022
DOI: 10.1002/fsn3.3040
|View full text |Cite
|
Sign up to set email alerts
|

Inulin‐type fructans and short‐chain fructooligosaccharides—their role within the food industry as fat and sugar replacers and texture modifiers—what needs to be considered!

Abstract: With the incidence of obesity and obesity-related diseases on the increase, the food industry is facing increasing pressure from both governmental and public health bodies to modify food products to reduce both fat and sugar intakes to help combat the burden of disease (Krystyjan et al., 2015;Rodriguez-Garcia et al., 2013). Both fat and sugar play vital roles in determining the physical, chemical, and, ultimately, sensory properties of several food products enjoyed by consumers, so it has become necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 199 publications
0
9
0
1
Order By: Relevance
“…In the past, an opposite effect has been reported [ 33 ]. This increase could be attributed to the fat-enhancing properties of oligofructose, which could lead to an increase in biscuit hardness [ 25 , 55 ]. The addition of lentil flour caused a significant increase in biscuits' F max , with the highest value observed for the samples containing 15 and 30% legume flour, independently of the sugar substitution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, an opposite effect has been reported [ 33 ]. This increase could be attributed to the fat-enhancing properties of oligofructose, which could lead to an increase in biscuit hardness [ 25 , 55 ]. The addition of lentil flour caused a significant increase in biscuits' F max , with the highest value observed for the samples containing 15 and 30% legume flour, independently of the sugar substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The findings were considered a starting point for future research and development of functional GF products. Oligofructose, a natural sugar comprising mainly of β -(2→1) fructosyl units ( n = 2 − 10), could be used for partial and/or total sugar substitution in biscuits, contributing to reduced caloric value while imparting sweetness [ 25 , 26 ]. Depending on its commercial grade, it could affect various quality characteristics as well as physicochemical, structural, texture, and sensory properties, necessitating further investigation when added to biscuit formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Acid hydrolysis was likely contributing to the apparent peak in inulinase activity at lower pH, while the second peak around pH 5 was due solely to inulinase activity. Acid-mediated hydrolysis of inulin at pH < 4 has previously been described (8). Additionally, we directly measured fructose concentration by HPLC at the end of the pH-modified inulinase activity assay.…”
Section: Effects Of Ph On Inulin Hydrolysis and Inulinase Activitymentioning
confidence: 99%
“…The prebiotic inulin, by contrast, is a long-chain fructan (Glu-Fru n ) with average DP > 10. Inulin is produced by several plants, such as Jerusalem artichoke (DP < 40), chicory root (DP < 100), and agave (8). Several clinical trials of inulin supplementation have demonstrated its utility as a prebiotic (4).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in a study that the combined use of inulin and stevia yielded improvement in the growth and activity of probiotic bacteria (Ozcan et al, 2021). Inulin is also used in the production of various types of food products as fat and sugar replacers and texture modifiers (Jackson et al, 2022; Mudannayake et al, 2022; Ozcan & Eroglu, 2022). Inulin has already been used in chocolate formulations by several researchers.…”
Section: Introductionmentioning
confidence: 99%